2023
DOI: 10.17582/journal.aavs/2023/11.9.1417.1427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycotic Mastitis and Evaluation of Some Virulence Potential of Candida albicans Isolated from Mastitic Goats

Abstract: The aims of this study are to identify mycotic agents, assess the prevalence of mycotic mastitis, and evaluate the virulence of C. albicans that was isolated from Mastitic goats. To investigate the prevalence of mycotic mastitis, related to goats in Baghdad, 166 lactating goats were examined and 332 milk samples were collected from ( January -July) 2022. 10 ml of milk were collected in sterile test tubes, an equal volume of milk and CMT reagent were gently shaken in a paddle and the reaction was noticed within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…In [43] reported that the prevalence of mastitis caused by yeasts was 1.09%, which also coincided with the results of our studies.…”
Section: Resultssupporting
confidence: 93%
“…In [43] reported that the prevalence of mastitis caused by yeasts was 1.09%, which also coincided with the results of our studies.…”
Section: Resultssupporting
confidence: 93%